AWARENESS ABOUT HARMFUL EFFECTS OF AEROSOL CONTAMINATION AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Possible mechanisms for the transmission of disease in the dental office include close communication with body fluids of patients, interaction with surfaces and instruments that have already been besmirched by the patient, and also interaction with unavoidable particles from the patient that have been dispersed airborne. This survey was performed with the purpose of assessing the awareness about the harmful effects of aerosol contamination in clinical practice among the dental students. A questionnaire containing ten questions about the awareness and attitudes of dental students toward the harmful effects of aerosol contamination in clinical practice. Then this questionnaire was piloted and distributed to 100 dental students, and information about the opinions and attitudes of dentists on aerosol contamination was collected. Salivary transmission of aerosols, procedures causing aerosol contamination, use of rubber dams in preventing contamination, and use of personal protection equipment were obtained. The collected data were statistically analyzed. 87% of the students were aware of the harmful effects of aerosol contamination. 78% were aware of the salivary transmission of aerosol contamination. The awareness about the harmful effects of aerosols is adequate among dental students. It is conceivable to limit the hazard with generally basic and reasonable safety measures.